Strategi Komunikasi Content Creator Podcast Disabilitas Sebagai Platform Peningkatan Disability Awareness - Kisyono, Gerry Akbar; Fiaji, Noveria Anggraeni (Universitas Brawijaya, 2022)
This research aims to explore the communication strategies employed by disabled content creators in podcasts to enhance disability awareness among their audience. The utilization of podcast platforms for disseminating disability awareness by content creators Afif, Argya, and Dhani is motivated by various factors, such as ease of use and wider dissemination beyond the limitations of space and time. Their podcast content educates the general public about disability awareness, aiming to challenge the prevailing stigma surrounding disabled individuals. By employing their respective communication strategies to package the messages conveyed in their podcast content, they aspire to make their educational efforts accessible to a broader audience. This study adopts a qualitative approach with a case study method. Data collection involves observation and interviews with the three research subjects. The findings reveal that all three creators have communication strategies aligned with the developmental communication and empowerment perspectives. Additionally, the research identifies that the three creators engage in innovation diffusion to enhance disability awareness within society. The study also outlines the stages involved in the creation and dissemination of podcast content by these creators. The responses received after creating podcast content include both positive and negative feedback. Positive feedback includes increased knowledge and behavioral changes experienced by the listeners, indicating the effectiveness of the communication strategies employed. Consequently, the messages conveyed are not only well-received but also put into practice by the audience. On the other hand, negative feedback indicates the persistence of negative prejudices from some listeners concerning the experiences shared by disabled creators.